Cobalt Sulfide/Nickel Sulfide Heterostructure Directly Grown on Nickel Foam: An Efficient and Durable Electrocatalyst for Overall Water Splitting Application - Shit, Subhasis; Chhetri, Suman; Fang, Wooree; Murmu, Naresh C.; Koo, Hyeyoung; Samanta, Pranab; Kuila, Tapas (American Chemical Society, 2018)
Fabrication of high-performance noble-metal-free bifunctional electrocatalysts for both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in water is a promising strategy toward future carbon-neutral economy. Herein, a one-pot hydrothermal synthesis of cobalt sulfide/nickel sulfide heterostructure supported by nickel foam (CoSx/Ni3S2@ NF) was performed. The Ni foam acted as the three-dimensional conducting substrate as well as the source of nickel for Ni3S2. The formation of CoSsx/Ni3S2@NF was confirmed by X-ray diffraction and X-ray photoelectron spectroscopy. The formation of CoSx/Ni3S2@NF facilitated easy charge transport and showed synergistic electrocatalytic effect toward HER, OER, and overall water splitting in alkaline medium. Remarkably, CoSx/Ni3S2@NF showed catalytic activity comparable with that of benchmarking electrocatalysts Pt/C and RuO2. For CoS,INi3S2@NF, overpotentials of 204 and 280 mV were required to achieve current densities of 10 and 20 mA cm(-2) for HER and OER, respectively, in 1.0 M KOH solution. A two-electrode system was formulated for overall water splitting reaction, which showed current densities of 10 and 50 mA cm(-2) at 1.572 and 1.684 V, respectively. The prepared catalyst exhibited excellent durability in HER and OER catalyzing conditions and also in overall water splitting operation. Therefore, CoSx/Ni3S2@NF could be a promising noble-metal-free electrocatalyst for overall water splitting application.
Keywords: OXYGEN EVOLUTION REACTION; NI3S2 NANOSHEET ARRAYS; HYDROGEN EVOLUTION; NI-FOAM; BIFUNCTIONAL ELECTROCATALYST; NANOWIRE ARRAYS; ACTIVE ELECTROCATALYST; ENHANCED ACTIVITY; ALKALINE MEDIA; ELECTRODE